Cytotoxic Molecules as Potential Biomarkers for Active and Inactive Systemic Lupus Erythematosus - Paola Santana-Sánchez; Astrid Asminda Ramírez-Pérez; Paolo Alberti-Minutti; Julián A. Gajón; Laura C. Bonifaz; Norberto Sánchez-Escobar; María Victoria Legorreta-Haquet; Luis Chávez-Sánchez; Adriana Karina Chávez-Rueda (Biomedicines)
Objectives: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder characterized by persistent inflammation. Reliable biomarkers for predicting disease reactivation are lacking. This study aimed to investigate serum cytokines and cytotoxic molecules in both the inactive (iSLE) and active (aSLE) phases to identify potential predictors of disease activity. Methods: Fifty-five SLE patients were classified as having iSLE (n = 36) or aSLE (n = 19) on the basis of clinical parameters and the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K). Serum levels of cytokines, cytotoxic molecules, and CD8+ cells were analyzed through flow cytometry and principal component analysis (PCA). Additionally, seventeen healthy donors (HDs) served as a control group. Results: Serum perforin (median: 2219 pg/mL; p = 0.0020) and granulysin (median: 1347 pg/mL; p = 0.010) levels were significantly higher in patients with aSLE than in patients with iSLE. In contrast, sFas levels were elevated in both SLE groups compared with those in the HD group. Moreover, increased perforin and granulysin levels were correlated with increased SLEDAI-2K scores, and the proportion of cytotoxic cells (CD8+granzyme-B+perforin+ cells) was correlated with disease activity. Conclusions: The increased levels of cytotoxic molecules and the high CD8+ cell proportions suggest that integrating these parameters with traditional biomarkers could enhance disease monitoring and management.